Prognostic Significance of Inflammatory and Nutritional Indices for Serous Ovary Cancer - Yan Han; Weiqin Lv; Jianfei Guo; Yun Shang; Fan Yang; Xiaomin Zhang; Keyuan Xiao; Liang Zong; Wenqing Hu (Clinical and Experimental Obstetrics & Gynecology)
Background: Cancer prognoses have been indicated to be associated with Onodera’s prognostic nutritional index (OPNI), the neutrophil-to-lymphocyte ratio (NLR), the platelet-to-lymphocyte ratio (PLR), and the systemic immune-inflammatory index (SII). We investigated the prognostic value of the OPNI, NLR, PLR, and SII for serous ovary cancer (SOC). Methods: We retrospectively analyzed the cases of 133 patients with SOC treated at our institution from 2014 to 2021. The survival of the patients was assessed utilizing the Kaplan-Meier method to analyze overall survival (OS). Additionally, a multivariate analysis employing the Cox proportional hazard regression model was conducted to identify the independent prognostic factors for SOC. The positive event for the ROC diagnosis is mortality during follow-up. Results: The results revealed the following optimal cut-off points: OPNI, 45.5; NLR, 2.3; PLR, 224.4; and SII, 747.5. A comparative analysis demonstrated significant differences between high- and low-OPNI score groups in the treatment method, tumor stage, lymph node metastasis, albumin, NLR, PLR, and SII; other indicators are not irrelevant. We also observed that the OPNI, NLR, PLR, and SII were related to OS: the OPNI score was positively correlated with OS whereas the NLR, PLR, and SII values were negatively correlated with OS. These results identified the OPNI as the best prognostic indicator for SOC. Conclusions: Our findings demonstrate that the OPNI, NLR, PLR, and SII could be used as predictive and prognostic parameters for SOC.